Spectrophotometric determination of paracetamol in drug formulations with 1 – naphthol - Iorhemen, Raymond T.; Iorhemba, Aondona M.; Sambo, Royalty E.; Nande, Winifred U. (International Journal of Advanced Chemistry, 2017)
Paracetamol with 1-Naphthol gave an azodye and the concentration of paracetamol was investigated spectrophotometrically. The dye formed with 1-Naphthol as a coupling agent followed Beer Lambert’s law within the range of 2 – 10 μgmL-1 of paracetamol at a lambda max (λmax) of 505nm. The molar absorptively of the azodye coupled with 1-Naphthol was found to be 1.6973×104 dm3mol-1cm-1, r2 was 0.9974. P value was found to be 0.013 at 95% confidence. LOD was 0. 02 μgmL-1 while LOQ was 0. 10 μgmL-1. The coupling agent has been applied successfully for the analysis of paracetamol in pharmaceutical preparations such as boska, ibex, mixagrip, norgesis and procold with the recovery of 101.27 %, 98.98 %, 99.47 %, 98.28 % and 101.6 % respectively. The relative standard deviation of all the five samples ranged from 0 % to 0.76 %. The method used in the present study may be applied to the determination of trace amount of paracetamol on clinical samples as it is simple, accurate and precise, and also reproducible.